Strategi pemasaran melalui media sStrategi Pemasaran Melalui Media Sosial (Tik Tok) Pada UMKM Dalam Perspektif Ekonomi Islamosial (tik tok) pada UMKM dalam perspektif ekonomi islam - Oktavia, Rima (IQTISADIE: Journal of Islamic Banking and Shariah Economy, 2025)
Marketing is an effort to provide and deliver the right goods and services to consumers by considering aspects of location, time, price, promotion, and effective communication. This study uses a qualitative approach. The types of data are primary and secondary taken from interviews and observations analyzed using qualitative descriptive. Case studies show that several local brands such as Tulus Signature and Ghaffa The Label have succeeded in increasing turnover and engagement through creative marketing strategies on Tik Tok. However, obstacles such as a lack of understanding of optimizing Tik Tok features are still a challenge for MSMEs. Therefore, it is important to develop an effective digital marketing strategy and identify the obstacles faced by MSMEs in utilizing social media platforms to increase sales